Strategi Pesantren dalam Pemberdayaan Ekonomi Masyarakat dan Bimbingan Karir Santri - Darussalam, Hidayat; Gustin, Gustin; Mulyono, Edi (Department of Islamic Guidance and Counseling, 2024)
At present, the role of pesantren (Islamic boarding schools) in empowering the community's economy is considered suboptimal and still focused solely on educational activities. Even if there are business units in the pesantren, these units only serve as income sources for the pesantren itself. This type of research is the result of data collection from field research, processed qualitatively using a descriptive method. Data collection methods include interviews, observations, and documentation. The existing data will be analyzed systematically to make it easy to interpret and understand. The research results conclude that the strategy of pesantren in economic empowerment is to utilize the Pesantren Cooperative (Kopontren). Then, efforts for career guidance for students are conducted through four patterns: 1) career guidance through economic activities centered on the kyai (religious leader); 2) career guidance for students through pesantren economic activities; 3) career guidance for students through economic activities for students; 4) career guidance for students through economic activities for alumni.